Peningkatan Kapasitas Tata Kelola Klaim BPJS Kesehatan melalui Edukasi Partisipatif Berbasis Problem-Solving pada Tim Casemix - Asmaryadi Asmaryadi; Nurfadhilah; Nurintan Malik; A. Karlina Askarini Makkasau; Ra’idatusakinah M. Nur; Ahmad Jayadi; Andi Nur Abidah Ramadhani; Hilmy Sakina Garmawi (LOSARI DIGITAL, 2026)
The management of INA-CBGs (Indonesian Case Based Groups) claims is a critical component of hospital governance and financial sustainability within the National Health Insurance era. Hospitals newly partnering with BPJS Kesehatan generally encounter challenges such as limited human resources, weak cross-unit coordination, and the absence of standardized claim management systems. This community service initiative aims to enhance claim governance capacity through a problem-solving-based participatory educational approach. The activity was conducted in 2025 at a hospital in Makassar, involving 27 participants: 4 members of the casemix team, 20 healthcare practitioners (Professional Care Providers), and 3 management representatives. The methods employed included initial assessments, interactive education, case-based discussions, and reflective evaluation. Data were collected through semi-structured interviews and observations, followed by a thematic analysis. The results identified primary challenges including limited coding competencies, suboptimal integration of hospital information systems, and the lack of standard operating procedures (SOP) for claims. Post-activity evaluation indicated an improvement in participants' understanding. The casemix team leader demonstrated the ability to delineate claim stages according to BPJS Kesehatan regulations and outline corrective measures for pending claims. Coders were able to identify the essential documentation requirements prior to claim submission. Furthermore, healthcare practitioners and management clarified their respective roles in ensuring claim success. This initiative also produced a draft of the primary claim management SOP and a document completeness checklist as practical outputs. Nevertheless, the long-term impact of these activities requires further evaluation based on more specific quantitative success indicators.